How do we recall the story of our lives? Evidence for a temporal order in the recall of important life story events. Issue 7 (9th August 2022) - Nusser, Lisa; Wolf, Tabea; Zimprich, Daniel
ABSTRACT: Based on the chronological nature of extensive life narratives, in two studies, we investigated whether a temporal order can also be found for the retrieval of important life story events. The data of Study 1 come from 52 older adults ( Mage  = 70.35, SDage  = 6.09) who reported seven important events from their life. We used multilevel analysis to take into account the hierarchical structure of the data but also to investigate individual differences. Results showed a significant temporal order effect which considerably differed between persons. In further exploratory analyses using group-based modelling, we identified three groups that differed in the direction (i.e., forward and backward) and in the size of the temporal order effect. The use of life scripts was not associated with a forward temporal order. Study 2 was conceptualised as a replication study and included 88 participants ( Mage  = 68.60, SDage  = 6.63) who recalled up to 15 important life events. The temporal order effect, as well as the three trajectories of temporarily ordering important life story events, were replicated. Again, the use of life script was not associated with a forward ordered recall. Potential explanations for a forward and backward temporal recall order are discussed.